Numerical Comparison of Two Runners for Gravitational Vortex Turbine - RUIZ SÁNCHEZ, Alejandro; GUEVARA MUÑOZ, Angie; SIERRA DEL RIO, Jorge Andrés; POSADA MONTOYA, Jose Alejandro (Engineering Transactions, 2021)
The main purpose of this study is to compare numerically the torque generated by two runners for a gravitational vortex turbine. One of the runners was an H-Darrieus turbine with the rotational flow into the chamber that helped to decrease its negative torque. The other runner was a standard (straight blade) turbine, which determined the performance in both cases. The study was conducted in ANSYSrCFX, where the model was configured at constant operating conditions in both cases. The standard runner performance was higher (75%) than that of the H-Darrieus runner. The highest torque for the standard and the H-Darrieus runners was 0.76 and 0.16 N·m, respectively. The standard runner had a larger fluid contact area than the H-Darrieus runner, which extracted more energy.